2019
DOI: 10.12669/pjms.36.2.732
|View full text |Cite
|
Sign up to set email alerts
|

Medical error reporting software program development and its impact on pediatric units’ reporting medical errors

Abstract: Objective: The purpose of this quasi-experimental study was to developing web-based, anonymous reporting system to increase reporting of medication errors, blood transfusion errors and patient falls in pediatric units and to compare the computerized system with the written system already in use at the institution. Methods: This study was conducted in all pediatric units of a research hospital. All physicians and nurses working in these units agreed to participate in the study. All units were visited to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Many studies, mostly international, reported the lack of a reporting system as a barrier to reporting [22,29,35]. A number of studies showed better reporting with electronic systems compared to paper reporting [45].…”
Section: Poor Understanding Of Me and The Importance Of Reporting Mementioning
confidence: 99%
“…Many studies, mostly international, reported the lack of a reporting system as a barrier to reporting [22,29,35]. A number of studies showed better reporting with electronic systems compared to paper reporting [45].…”
Section: Poor Understanding Of Me and The Importance Of Reporting Mementioning
confidence: 99%
“…A negative attitude means that the employee has a low awareness of the importance of medical errors and error reporting; a positive attitude means that the employee has a high awareness of the importance of medical errors and error reporting. In other studies, the internal consistency reliability coefficient has ranged between 0.66 and 0.76 for the whole scale 39,40 . In this study, the scale's internal consistency was 0.76.…”
Section: Methodsmentioning
confidence: 51%
“…In other studies, the internal consistency reliability coefficient has ranged between 0.66 and 0.76 for the whole scale. 39,40 In this study, the scale's internal consistency was 0.76.…”
Section: Strategy 5: Patient Safety Symposiummentioning
confidence: 58%
“…Employees who report and act on nursing errors are rewarded and empowered in patient safety culture. (Is there a safety culture that helps employees overcome their fear of repercussions and creates a work environment that encourages mistake identification and reporting (Unal & Intepeler, 2020).…”
Section: Discussionmentioning
confidence: 99%